Sacred Forest Degradation and Conservation: Resident Views of Nakpadjoak Forest in Togo, West Africa - Brandon Franta; Yendoubouam Kourdjouak; Lin-Ernni Mikégraba Kaboumba; Nico Arcilla (Conservation, 2025)
Historically protected by cultural traditions, sacred forests are now increasingly threatened by anthropogenic pressures, particularly in West Africa, where natural areas and wildlife populations have dwindled as human populations have increased exponentially. Residents in the vicinity of sacred forests play critical roles in conservation success or failure, but few studies have investigated their views. We surveyed 281 residents representing ~100% of households surrounding the sacred forest of Nakpadjoak, a 50-hectare remnant of Sudan-Guinea woodland savanna in northern Togo that is now surrounded by human-dominated landscapes. The majority of residents believe that the sacred forest should be protected (92%) and that access to the forest should be prohibited (55%). Most residents own livestock (93%) and reported that the forest has become a pasture for domestic animals (70%) while wildlife populations have declined (79%). Two-thirds of residents (64%) reported that the forest has changed due to wood cutting, a practice that occurs despite being banned. Most (96%) residents use wood as their primary source of domestic energy, but 90% would switch to alternative fuels, such as natural gas, if available. Unfortunately, despite residents’ desire to protect the forest and external funding for its protection and restoration, Nakpadjoak forest has become increasingly degraded due to ongoing exploitation and conflicts of interest surrounding its use. We recommend bolstering local prohibitions on sacred forest exploitation as well as government interventions such as subsidizing natural gas as an alternative to wood fuel to support the conservation of this and other protected areas in the region, which may otherwise be destroyed.